2008
DOI: 10.1021/jp803210w
|View full text |Cite
|
Sign up to set email alerts
|

Structural Transformation of LiVOPO4 to Li3V2(PO4)3 with Enhanced Capacity

Abstract: In the present investigation, we report the transformation of alpha-LiVOPO 4 to alpha-Li 3V 2(PO 4) 3, leading to an enhancement of capacity. The alpha-LiVOPO 4 sample was synthesized by a sol-gel method, followed by sintering at 550-650 degrees C in a flow of 5% H 2/Ar. The structural transformation of a triclinic alpha-LiVOPO 4 structure to a monoclinic alpha-Li 3V 2(PO 4) 3 structure was observed at higher sintering temperatures (700-800 degrees C in a flow of 5% H 2/Ar). The alpha-Li 3V 2(PO 4) 3 phase was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 28 publications
0
40
1
Order By: Relevance
“…2c). The refined lattice parameter values are slightly lower and the lattice volume of the monoclinic unit cell is significantly lower in the present Li 3 V 2 (PO 4 ) 3 /C than those reported51120293031323334. In general, the reported lattice volume for LVP/C is relatively higher than that for pure LVP.…”
Section: Resultscontrasting
confidence: 65%
“…2c). The refined lattice parameter values are slightly lower and the lattice volume of the monoclinic unit cell is significantly lower in the present Li 3 V 2 (PO 4 ) 3 /C than those reported51120293031323334. In general, the reported lattice volume for LVP/C is relatively higher than that for pure LVP.…”
Section: Resultscontrasting
confidence: 65%
“…Also, it is greater than the capacity values reported by Zhong et al (119 mAh g À1 ) [20] for the combustion synthesized Li 3 V 2 (PO 4 ) 3 /C cathode, which is noteworthy. Similarly, the capacity values of 174 mAh g À1 (C/10 rate), 160 mAh g À1 C/5 rate) and 96 mAh g À1 (10C rate) exhibited by Li 3 V 2 (PO 4 ) 3 /C (850 8C) cathode in the 4.8 V limit corresponding to the extraction of three lithium per formula unit are either comparable [21] or superior [22,23] than the reported values, with an exception of two [24,25].…”
Section: Charge-discharge Studiesmentioning
confidence: 49%
“…For the isotypic Li 3 Fe 2 (PO 4 ) 3 structure, see: Patoux et al (2003). Structural studies of Li 3 V 2 (PO 4 ) 3 based on powder diffraction data have been reported previously by Yin et al (2003); Patoux et al (2003); Kuo et al (2008); Yang et al (2010); Fu et al (2010). For ionic radii, see: Shannon (1976).…”
Section: Related Literaturementioning
confidence: 97%
“…Data collection: RAPID-AUTO (Rigaku, 2006); cell refinement: RAPID-AUTO; data reduction: RAPID-AUTO; program(s) used to solve structure: SHELXS97 (Sheldrick, 2008); program(s) used to refine structure: SHELXL97 (Sheldrick, 2008); molecular graphics: DIAMOND (Brandenburg, 1999); software used to prepare material for publication: WinGX (Farrugia, 2012). Trilithium divanadium(III) tris(orthophosphate), Li 3 V 2 (PO 4 ) 3 , has been investigated as a cathode material of secondary batteries (Yin et al, 2003) and its structure has been reported based on powder diffraction data (Yin et al, 2003;Patoux et al, 2003;Kuo et al, 2008;Yang et al, 2010;Fu et al, 2010). In an attempt to prepare new mixed-metal phosphates using LiCl as a flux, we were able to isolate crystals of Li 3 V 2 (PO 4 ) 3 , and report here the results of the structure analysis based on single-crystal X-ray diffraction data.…”
Section: Data Collectionmentioning
confidence: 99%